2016
DOI: 10.3847/0004-637x/830/1/13
|View full text |Cite
|
Sign up to set email alerts
|

Host-Galaxy Properties of 32 Low-Redshift Superluminous Supernovae From the Palomar Transient Factory

Abstract: We present ultraviolet through near-infrared photometry and spectroscopy of the host galaxies of all superluminous supernovae (SLSNe) discovered by the Palomar Transient Factory prior to 2013 and derive measurements of their luminosities, star formation rates, stellar masses, and gas-phase metallicities. We find that TypeI (hydrogen-poor) SLSNe (SLSNe I) are found almost exclusively in low-mass ( * <´ M M 2 10 9) and metal-poor (12+log 10 [O/ H] < 8.4) galaxies. We compare the mass and metallicity distribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
346
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(392 citation statements)
references
References 140 publications
(220 reference statements)
38
346
3
5
Order By: Relevance
“…Lee et al 2004;Peeples et al 2009). This is also seen for other SLSN type I host galaxies with disturbed morphologies (Lunnan et al 2015;Perley et al 2016). However, none of the three systems in LSQ14mo have particularly high sSFR or low Z g for their stellar mass.…”
Section: Interacting Galaxy Systemmentioning
confidence: 72%
“…Lee et al 2004;Peeples et al 2009). This is also seen for other SLSN type I host galaxies with disturbed morphologies (Lunnan et al 2015;Perley et al 2016). However, none of the three systems in LSQ14mo have particularly high sSFR or low Z g for their stellar mass.…”
Section: Interacting Galaxy Systemmentioning
confidence: 72%
“…If FRBs are indeed more commonly hosted by dwarf galaxies in the low-redshift universe, they would share this preference with two other classes of high-energy transientslong-duration gamma-ray bursts and superluminous supernovae, both of which prefer low-mass, low-metallicity, and high star formation rate hosts (e.g., Fruchter et al 2006;Perley et al 2013Perley et al , 2016Vergani et al 2015; and other works). Indeed, superluminous supernovae are preferentially hosted by EELGs (Leloudas et al 2015).…”
Section: Relation To Dwarf Galaxiesmentioning
confidence: 99%
“…If an object like ASASSN-15lh, which peaked at −23.5 mag, were indeed an SLSN (Dong et al 2016;Godoy-Rivera et al 2017), it would be significantly more extreme than any of the objects found in PS1MDS. Given this transient's location at the center of a massive galaxy (while SLSN-I are almost exclusively found in low-mass, lowmetallicity galaxies; e.g., Lunnan et al 2014Lunnan et al , 2015Leloudas et al 2015;Perley et al 2016), it has also been suggested that this transient was a tidal disruption event rather than a true SLSN (Perley et al 2016;Leloudas et al 2016;Margutti et al 2017b). …”
Section: Luminosity Function Of H-poor Slsnementioning
confidence: 99%